Manajemen Kehadiran dan Pembinaan Disiplin Peserta Didik: Studi Kasus di SMP Negeri 33 Makassar - Andi Ratu Ayuashari; Andi Tenri Abeng (Yayasan Abdurrauf Cendekia Nusantara, 2026)
Student attendance management and discipline development play an important role in creating an orderly and conducive learning environment. However, studies that integrate attendance systems with discipline development strategies within the framework of student management at the junior secondary school level remain limited, particularly in practical school contexts. This study aims to analyze the implementation of attendance systems and discipline development strategies for students at SMP Negeri 33 Makassar. This research employs a qualitative approach with a field research design. Data were collected through interviews with homeroom teachers, guidance and counseling teachers, and the vice principal for student affairs, supported by school documentation. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the attendance system implemented combines manual and digital methods to improve the accuracy of monitoring student attendance. Discipline development is carried out in stages through the roles of homeroom teachers, guidance and counseling teachers, and coordination with parents and school authorities. In addition, the implementation of a point-based system for violations and positive behavior serves as an educational discipline strategy without the use of physical punishment. The findings highlight that collaboration among teachers, school leaders, and parents is a key factor in improving student discipline and attendance. This study contributes to strengthening educational management practices through an integrated model of attendance management and character-based discipline development in schools. [Manajemen kehadiran dan pembinaan disiplin peserta didik memiliki peran penting dalam menciptakan lingkungan belajar yang tertib dan kondusif. Namun, kajian yang mengintegrasikan sistem absensi dengan strategi pembinaan disiplin dalam perspektif manajemen peserta didik di tingkat sekolah menengah pertama masih terbatas, khususnya dalam konteks praktik di sekolah. Penelitian ini bertujuan untuk menganalisis implementasi sistem absensi serta strategi pembinaan disiplin peserta didik di SMP Negeri 33 Makassar. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian lapangan. Data dikumpulkan melalui wawancara dengan wali kelas, guru bimbingan dan konseling (BK), serta wakil kepala sekolah bidang kesiswaan, yang diperkuat dengan dokumentasi kegiatan sekolah. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa sistem absensi yang diterapkan menggunakan kombinasi manual dan digital untuk meningkatkan akurasi pemantauan kehadiran siswa. Pembinaan disiplin dilakukan secara bertahap melalui peran wali kelas, guru BK, serta koordinasi dengan orang tua dan pihak sekolah. Selain itu, penerapan sistem poin pelanggaran dan poin positif menjadi strategi pembinaan disiplin yang bersifat edukatif tanpa hukuman fisik. Temuan penelitian menegaskan bahwa kolaborasi antara guru, pimpinan sekolah, dan orang tua menjadi faktor kunci dalam meningkatkan kedisiplinan dan kehadiran peserta didik. Penelitian ini berkontribusi pada penguatan praktik manajemen pendidikan melalui model pengelolaan kehadiran yang terintegrasi dengan pembinaan disiplin berbasis karakter di lingkungan sekolah.]